The first earthworm collections from Nicaragua with description of two new species (Oligochaeta) - Sherlock, Emma; Lee, Stewart; Mcphee, Sally; Steer, Mark; Maes, Jean Michel; Csuzdi, Csaba (Zootaxa, 2011)
In August 2009 the Natural History Museum London, Hungarian Natural History Museum and Systematic Zoology Research group, Entomological Museum in Leon and The Society for Environmental Exploration, mounted the first earthworm collection expedition to Nicaragua. No native earthworm species had previously been recorded for this country. This paper lists 18 new species records for the Country with the description of two new taxa to science: Eutrigaster (Graffia) azul sp. n. and Eutrigaster (Graffia) nicaraoi sp. n. New data on the species Eutrigaster (Eutrigaster) oraedivitis Cognetti, 1904 is also presented here.